DEVELOPMENT OF 6 GHZ TRANSCEIVER FOR OBJECT DETECTION RADAR - Pradhana N.P., Alvandhyto
The growth in the number of vehicles, especially four-wheeled vehicles in Indonesia, is getting faster every year, especially with the many credit schemes that make it easier for consumers to own their dream vehicles. But unfortunately, the vehicle safety regulations in Indonesia are not strict enough so that many of the four-wheeled vehicles marketed in our country are far behind vehicles marketed in other countries, especially in terms of ADAS technology. This research aims to develop one of the many forms of ADAS, namely FMCW-based object detection